Practicing BizMath challenge modul for primary schools based on the STREAM Curriculum / Zarith Sofiah Othman … [et al.] - Othman, Zarith Sofiah; Tukiman, Norbaiti; Khalid, Ahmad Khudzairi; Ahmad, Nur Intan Syafinaz (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
The learning process has evolved tremendously over time. Notably, in the 21st century, different types of technologies are used to make learning accessible anytime and anywhere to a generation of students who were brought up during the age of digital technology and are familiar with computers and the internet from an early age. Thus the Science, Technology, Engineering and Mathematics.(STEM) approach aims to help these students understand and learn in the best way. The objective of this paper is to build up students skill through their interest in Science, Technology, Reading, Art, Mathematic.(STREAM) module. This paper focusses on one such way that is mathematical learning outside the classroom. The ‘BizMath Challenge’ modul is an innovative project that is based on the curriculum of STREAM and fulfills the mathematics syllabus at the primary school level. The curriculum of STREAM is applied in this project to nurture the values of learning through the five scopes of education. In addition, the concepts of IQ (Intelligent Quotient), EQ (Emotional Quotient), problem solving and innovation design are also employed. To measure the variables of the study, a Likert scale ranging from 1 (strongly disagree) to 5 (strongly agree) is used. R statistics programming is used to run the descriptive analysis and correlation analysis. The results show that the BizMath Challenge brings benefits students’ learning by improving their mathematical skills and knowledge. Conventional methods are deemed less attractive to these students who prefer learning outside their classrooms as they can connect the lessons with their environment and everyday life. Therefore, educators need to do a great job in preparing the change based on learning activities and should start getting acquainted with STREAM projects.